Does conformity occur during students’ decision making for their careers? - Fadilla, Putri Fathia; Abdullah, Sri Muliati; Wu, Mingchang (Asian Journal of Assessment in Teaching and Learning, 2020)
Students between ages 13 to 18 years old are exposed to have career development assignments of life focused on the education field such as choosing majors or career fields. Students see career decision making is always accompanied by feelings of doubt, uncertainty, and even stress. In the end, students make their choice on careers by just following the decisions of their peers, which is not necessarily the right decision for them. Their decision taken can lead to career success. The purpose of this study to determine the effect of the conformity of students’ decision making for their careers. The quantitative research methods are used where the samples are 136 students of class XII. Data are obtained from the Likert scale instrument and analyzed using regression analysis. The result shows there is influence between conformity and students’ decision making for their career. The findings of the research are the categorization score of conformity is in high category with 60.29%, while the variable of career decision making is in the low category with 54.41%. Thus, the coefficient value is -0.573 (p<0.01) with an effective contribution of 32.9% and the remaining is 67.1% is determined by other variables, which are not considered in this research. This shows that the higher of conformity, so the lower of career decision making in the class XII students. Hence, this study is essential to provide a view on the importance of career decision making abilities that will affect the students’ future.